PENGARUH NILAI PELANGGAN DAN CITRA MEREK TERHADAP LOYALITAS MEREK MELALUI KEPERCAYAAN MEREK SEBAGAI VARIABEL INTERVENING PADA NOTEBOOK TOSHIBA (STUDI PADA MAHASISWA UNIVERSITAS DIPONEGORO SEMARANG) - Aprilian Wulan; Apriatni Endang Prihatini; Sendhang Nurseto (Universitas Diponegoro, 2014)
The research was motivated by the increasing of competition among the competitors on the notebook industry. Specifically, this research discusses the Toshiba brand notebook which is included in the top three notebook vendors in Indonesia. Toshiba notebook was experiencing decline in sales volume (2012-2013), followed by decreasing in the percentage of Top Brand Index (2010-2014). The purpose of this research is to examine the influence of customer value and brand image towards brand loyalty through brand trust in Toshiba Notebook. The type of this research is explanatory. The method of collecting data using questionnaire and interview. The technique of sampling using purposive sampling. The sample in this research is 100 respondents. Measurement scale using Likert Scale. Linear regression analysis and path anlysis were used to test the hypotheses using SPSS 16.0. The study results indicate that both simultaneously and partially, customer value and brand image have positive influence towards dependent variable, namely brand trust and brand loyalty. However, descriptive analysis of the perception of the respondents indicate that customer value, brand image, and brand loyalty still were perceived less by a few respondents. Based on the results of path analysis, the direct infulence of customer value and brand image towards brand loyalty is greater than the indirect influence of customer value and brand image towards brand loyalty through brand trust.